2014
DOI: 10.1002/poc.3294
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical mechanistic studies on the degradation of alizarin yellow R initiated by hydroxyl radical

Abstract: The degradation of azo dyes has attracted many research efforts not only due to the resulting environmental problems but also because the azo compounds with various substituents may show different degradation mechanism. It has been computationally found here, for the first time, that the HO• initiated cleavages of C-N and N-N bonds of alizarin yellow R with carboxyl group are kinetically competitive. In view of the formation of HO• adducts, the C-N and N-N bond cleavages of the hydrazone tautomer of alizarin y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
4
11
0
Order By: Relevance
“…They found that for AYRA, the C-N bond cleavage is kinetically competitive with, but thermodynamically more favorable than the N-N bond cleavage. 55 Their conclusion is in line with the corresponding experimental nding, that is, the phenol was observed as major product in the oxidation degradation of AYRA. 56 In the present paper, the dual descriptor result suggests that the attacks by cOH at both the N32 and N33 sites of the azo group, which are associated with the N-N bond cleavage, 55 are not favorite.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…They found that for AYRA, the C-N bond cleavage is kinetically competitive with, but thermodynamically more favorable than the N-N bond cleavage. 55 Their conclusion is in line with the corresponding experimental nding, that is, the phenol was observed as major product in the oxidation degradation of AYRA. 56 In the present paper, the dual descriptor result suggests that the attacks by cOH at both the N32 and N33 sites of the azo group, which are associated with the N-N bond cleavage, 55 are not favorite.…”
Section: Resultssupporting
confidence: 83%
“…Jiao et al 55 studied the OH-initiated C-N and N-N bond cleavages of alizarin yellow R (AYR, see Scheme 1) and its anion form (AYRA) computationally at the MPW1K/6-311+G(d,p)// B3LYP/6-31G(d) with the integral equation formalism polarized continuum model (IEF-PCM) used in the single point energy calculation. They found that for AYRA, the C-N bond cleavage is kinetically competitive with, but thermodynamically more favorable than the N-N bond cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…concluded that the reactions of Acid Orange 7 and 8 with •OH radical gave precedence to the C−N bond cleavage mechanism both kinetically and thermodynamically. In contrary, Jiao et al . in their study on neutral and anionic forms of Alizarin Yellow R reported that the C−N and the N−N bond cleavage pathways are kinetically competitive, but the former was found to be more thermodynamically favoured for the anionic form and the hydrazone tautomer only.…”
Section: Introductionmentioning
confidence: 91%
“…Previous theoretical studies by Ozen et al . and Jiao et al . gave conflicting reports on the degradation mechanisms of azo dyes such as Acid Orange 7, Acid Orange 8 and Alizarin Yellow R, which exist predominantly in hydrazone tautomeric form.…”
Section: Introductionmentioning
confidence: 99%
“…All calculations in this work were performed at the level of B3LYP/6-31G*, as planted in Gaussion 09 program [18]. Subsequent vibration frequency analyses were preformed for confirmation of the optimized structure as a minimum (N imag = 0).…”
Section: Theoretical Calculationsmentioning
confidence: 99%